2001
DOI: 10.1016/s1352-2310(00)00397-6
|View full text |Cite
|
Sign up to set email alerts
|

A mass transfer model for simulating VOC sorption on building materials

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 9 publications
0
34
0
2
Order By: Relevance
“…Children presenting with asthma who are sensitised and exposed to cockroaches are at higher risk of hospitalisation [58]. Also, exposure to pollutants such as formaldehyde and volcanic organic compounds, which are emitted from building materials have been associated with asthma, and bronchial obstruction in the first 24 months of life [59, 60]. Our study revealed that women who used biomass, water from unimproved sources and unimproved toilet facilities had experienced higher under-five deaths than those using clean fuel, improved water sources and improved toilet facilities respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Children presenting with asthma who are sensitised and exposed to cockroaches are at higher risk of hospitalisation [58]. Also, exposure to pollutants such as formaldehyde and volcanic organic compounds, which are emitted from building materials have been associated with asthma, and bronchial obstruction in the first 24 months of life [59, 60]. Our study revealed that women who used biomass, water from unimproved sources and unimproved toilet facilities had experienced higher under-five deaths than those using clean fuel, improved water sources and improved toilet facilities respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Many numerical models have been developed for simulating the surface emission of VOCs from building materials and decorating materials, and VOCs sorption (Won et al, 2001;Yang et al, 2001;Hodgson et al, 2002;Haghighat and Huang, 2003;Huang and Haghighat, 2003;Murakami et al, 2003;Zhang and Xu, 2003;Wilke et al, 2004;Xu and Zhang, 2004;Zhang and Niu, 2004;Kim and Kim, 2005;Lee et al, 2005;Li and Niu, 2005). Some experiments have also been performed to investigate VOCs diffusion inside the materials (Meininghaus and Uhde, 2002;Onwandee et al, 2005;Huang et al, 2006;Zhang et al, 2007).…”
Section: Primary Gaseous Pollutantsmentioning
confidence: 99%
“…It has been reported that the interaction between the surface and the bulk material can be described by Fick's Law using and equilibrium-interface model (Meininghaus & Uhde, 2002;Yang et al, 2001;Zhang, Zhang, Chen, & Yang, 2002;Zhao, Little, & Hodgson, 2002). Due to a lack of data on material properties and the complexity of the calculation, the interaction between the surface and the embedded sink is estimated by the onedimensional equation of Fick's law, using an effective mass transfer coefficient (Jørgensen et al, 2000;Singer et al, 2004):…”
Section: Agentmentioning
confidence: 99%